Mental Rehabilitation of Divorce Prohibition Victim Wives Through the Balancing Institution of Megou Pak Customary Pepung and its Implications Against Household Harmony - Asnawi, Habib Shulton (COUNS-EDU: The International Journal of Counseling and Education, 2024)
This article examines the role of Lembaga Penyimbang Pepung Adat Megou Pak in conducting mental rehabilitation of wives who are victims of domestic conflict. Lampung Megou Pak customary society has a rule called Mak Dijuk Siang (prohibition of divorce), but this customary rule has led to household disharmony, which has an impact on the wife's mental psychology. The question of this article is what impact does the implementation of the prohibition of divorce have on household harmony? What are the efforts of the Penyimbang Pepung Adat Megou Pak Institution in mentally rehabilitating the wives of victims of domestic violence? The method used is qualitative, the type of field research conducted in the Lampung Megou Pak indigenous community in Tulang Bawang Regency, the approach used is an ethnographic approach (ethnic approach), primary data sources are obtained from Lampung Pepadun Megou Pak traditional leaders and wives of victims of domestic violence. The results of the study found that the prohibition of divorce led to household disharmony, the wife became a victim of neglect of livelihood. The Penyimbang Pepung Adat Megou Pak institution plays a significant role in carrying out traumatic recovery of wives as victims of domestic violence, this traditional institution as a conflict resolution in mediating husband and wife and contributing to reconciling the parties and contributing to resolving household conflicts, so that divorce can be prevented.